Preparation and characterization of biocomposite films from kenaf-derived cellulose fibers and polylactic acid - Abd Rahman, Siti Hajar (2012)
The aim of this study was to produce kenaf derived cellulose-polylactic acid (KDCPLA) biocomposites and characterize its properties relevant to potential packaging application such as thermal properties and barrier properties against oxygen and water vapor. Other important bicomposite properties in the development of packaging material such as tensile and morphological analysis were also carried out. Kenaf bast fiber is a fiber which was used to derive cellulose via chlorination and mercerization processes. It was then designated as kenaf derived cellulose (KDC). The incorporation of KDC presents an alternative approach to achieve the intended properties. Thus, in this work, KDC loadings ranging from 0-60% were incorporated in the KDC-PLA biocomposite films. The KDC was found to be less thermal stable than the kenaf bast fiber. X-Ray Diffraction (XRD) spectrum revealed that the cellulose has relatively higher crystallinity index as compared to kenaf bast fiber which led to this phenomenon. In the case of biocomposite’s thermal stability, 6% lower degradation temperature was demonstrated when maximum 60% KDC incorporated in PLA matrix. The thermal properties of KDC-PLA biocomposite showed no major changes with KDC addition. This reflected by nearly unmodified crystallization temperature (Tc) of KDC-PLA biocomposite films. The additional loading of cellulose also shifted the melting temperature (Tm) value to the higher temperature. It means that by incorporating KDC into the PLA matrix have increases the melting point of biocomposite while percent of crystallinity (%Xc) showed no particular trend with additional loadings of KDC in biocomposite. With the additional KDC loading, the oxygen gas permeability was significantly reduced by 85% (shown by decrease in permeability value) but the water vapor permeability was increased by 91% for the highest KDC loading (60%). However the water vapor permeability is still acceptable as the value is within moderate water vapor permeability (50-100 g/m2/day). Composite properties on tensile strength and elongation at break were found reduced as compared to the neat PLA while tensile modulus was found increased showing that the stiffer biocomposite is produced with higher KDC loading. Proven with Environmental Scanning Electron Microscope (ESEM) micrograph, the reduced in tensile strength was due to weak interfacial adhesion between PLA matrix and KDC. Significant reduction in elongation at break suggested that a lower interfacial interaction effect and/or lack of optimum dispersion of KDC in biocomposite. This resulted biocomposite possibly has the potential application in the fruits and vegetables packaging field that require low oxygen gas permeability and moderate water vapor permeability.